A polymorphism of the CC16 gene is associated with an increased risk of asthma. Issue 6 (June 1998) - Laing, I A; Goldblatt, J; Eber, E; Hayden, C M; Rye, P J; Gibson, N A; Palmer, L J; Burton, P R; Le Souëf, P N
Abstract : Several quantitative traits associated with the asthma phenotype have been linked to markers on chromosome 11q13, although the gene responsible has yet to be well established. The gene for Clara cell secretory protein (CC16) is an ideal candidate for involvement in an inherited predisposition to asthma because of its chromosomal location, the role of the CC16 protein in controlling airway inflammation, and differences in levels of the protein between asthmatics and healthy controls. All three CC16 exons were screened in an unselected population of 266 subjects from 76 families and a cohort of 52 severely asthmatic children. A combination of single strand conformational polymorphism (SSCP) analysis, heteroduplex analysis, DNA sequencing, and restriction digestion was used. Mutation detection methods identified an adenine to guanine substitution in the CC16 gene at position 38 (A38G) downstream from the transcription initiation site within the non-coding region of exon 1. In the unselected population, 43.6% were homozygous for the polymorphic sequence (38GG) and 46.2% were heterozygous (38AG). All the asthmatic and unaffected children from both populations were selected for an unmatched case control analysis consisting of 67 asthmatic and 46 unaffected subjects. Those homozygous for the published sequence (38AA) had a 6.9-fold increased risk of developing asthma (p=0.049) and heterozygotes (38AG) a 4.2-fold increased risk (p=0.028). Modelling of genotype as a continuous covariate indicated evidence of a significant linear trend across the three genotypes (odds ratio=2.84 per unit increase in genotype code, p=0.018). These associations were independent of age, gender, and tobacco smoke exposure. These data and the known anti-inflammatory role of CC16 in the respiratory tract suggest that alteration to the gene at position 38 may contribute to asthma.